Developing and validating an instrument measuring school leadership. Issue 4 (4th July 2019) - Shen, Jianping; Ma, Xin; Gao, Xingyuan; Bierlien Palmer, Louann; Poppink, Sue; Burt, Walter; Leneway, Robert; McCrumb, Dennis; Pearson, Charles; Rainey, Mark; Reeves, Patricia; Wegenke, Gary
Abstract: In this study, we developed and validated an instrument that researchers can use to measure the collective effort of principals and teachers who excise their own unique leadership to generate (integrated) school leadership. Based on 644 teachers, we found sound psychometric properties of the scales of the instrument and the instrument as a whole. We also explored the predictive properties of the instrument in predicting student achievement at the school level. Based on 53 schools, we found that the instrument can indeed measure the kind of school leadership that really matters to student achievement. When predicting student achievement (at the school level), the instrument tends to be more sensitive to more difficult school subjects (e.g. mathematics), implying that improvement in school leadership would lead to larger improvement in student achievement (at the school level) in more difficult school subjects.